Recent progress in 2D inorganic/organic charge transfer heterojunction photodetectors - Han, Jiayue (2022)
2D materials possess superior optoelectronic properties, such as ultrahigh mobility and broadband photoresponse, making them one of the most vital platforms for diversified photodetectors. However, atomic thickness 2D materials usually suffer from intrinsic low absorption. To promote the photodetector performance, a feasible method is to integrate the 2D materials with low-cost, flexible, and tunable organics that form a charge transfer (CT) heterojunction. As results, in-depth multifunctional CT 2D-inorganic/organic detector exhibits extended functions such as low-power consumption, in-memory detection, and optical-bio synapse to meet the demand of contemporary photonic cell. Particularly, the progresses in wafer-scale monocrystal of both 2D and organic materials render vast potential applications with operation frequencies ranging from ultraviolet to terahertz. Here, the recent advances of 2D-inorganic/organic CT photodetectors are comprehensively reviewed by several classifications. Future developments and applications in optical biology, synapsis, and machine vision are also highlighted.